Neuronal activity in posterior parietal cortex area LIP is not sufficient for saccadic eye movement production - Brunamonti, Emiliano; Paré, Martin (Frontiers in Integrative Neuroscience, 2023)
It is widely recognized that the PPC play a role in active exploration with eye movements, arm reaching and hand grasping. Whether this role is causal in nature is largely unresolved. One region of the PPC appears dedicated to the control of saccadic eye movement. This lateral intraparietal (LIP) area possesses direct projections to well-established oculomotor centers and contains neurons with movement-related activity. Here we tested whether these neurons are implicated in saccade initiation and production. We submitted to test the movement-related activity of LIP neurons by recording their activity while monkeys performed a countermanding task. We found that LIP neuronal activity is not different before the execution or the cancellation of commanded saccades, and thereby not sufficient for the initiation and production of saccades. Consistent with the evolutionarily late emergence of the PPC, this finding relegates the role of this PPC area to processes that can regulate but not trigger eye movements.